ITO nanoparticles enhanced upconversion luminescence in Er3+/Yb3+-codoped silica glasses. Issue 7 (31st January 2018) - Chen, Ping; Hou, Shaodong; Yang, Yu; Chen, Zhangru; Yang, Luyun; Li, Jinyan; Dai, Nengli
Abstract : ITO nanoparticles enhanced upconversion luminescence in Er 3+ /Yb 3+ -codoped silica glasses. Abstract : Upconversion (UC) materials have shown many applications in the solar cell industry, biomedical imaging, and LED lighting. For the first time, we report enhanced UC in Er 3+ /Yb 3+ -codoped silica glasses induced by the energy transfer between rare earth ions and indium tin oxide nanoparticles (ITO NPs), introduced by an in situ growth approach. The enhancements of the intensities of the emissions of red and green light were all more than 10 fold and in some cases up to 42 fold. This work in our opinion has contributed a novel method and materials for UC enhancement in Er 3+ /Yb 3+ -codoped silica glasses.